GEOLOGY AND MODELLING RESERVOIR OF BATURAJA FORMATION IN PING FIELD, SOUTH SUMATRA BASIN - SARASWATI, ANANDYA
The PING Field is an oil and gas field located in the South Sumatra Basin. The field has been developed and covers an area of 50 km2. The objectives of this study are to determine the PING Field’s geological setting, detailed reservoir modelling, and the estimation of the original hydrocarbons in place. The reservoir modelling and hydrocarbon reserves estimates focus on the Baturaja Formation which is composed of limestone. The dataset used for this study includes well data from 55 wells in addition to the 2D seismic data. A total of four evaluation methods were undertaken in this study. These were; Well data analysis undertaking well-to-well correlation and petrophysical analysis; Seismic data analysis by generating a depth structure map and interpreting reservoir geometry; The integration of well and seismic data; Reservoir modelling using the 3D structure interpretation, petrophysical evaluation, original fluid contacts and the estimation of the original hydrocarbons in place. The key findings in the study are the stratigraphy, structure and setting of the PING field from seismic integration which details a northwest-southeast anticline associated with a thrust fault and a northeast-southwest oriented normal fault. The hydrocarbons are reservoired in a platform carbonate which ranges in thickness from 6.5 to 74 metres while the original hydrocarbons in place were 86 BSCF of gas and 37 MMSCF of oil.